THE DOCTRINE OF XENOPHANES FROM COLOPHON AND PARMENIDES FROM ELEA CONCERNING TEMPORAL AND SPATIAL INFINITY - D. V. Vorobiov; E. V. Smirnova (Вестник Мининского университета, 2018)
Introduction: the purpose of this article is to highlight the main difficulties and paradoxes, which are connected with temporal and spatial infinity and also to research their solutions in the context of the philosophy of Xenophanes from Colophon and Parmenides from Elea.Materials and Methods: the base of this article is various materials of Russian and foreign researchers, who have researched problem of the temporal infinity in the doctrine of Eleatics with different approaches. In this article the methodology of critical analysis of the researched materials is used, combined with the methods of comparative analysis of doctrine of Xenophanes and doctrine of Parmenides from Elea.Results: the point of view according to which the Being of Xenophanes and Parmenides exists in time and space and  has the shape of a non-hollow sphere is researched in this article. Together with justification of the first point of view, there is another point of view according to which the Being of Xenophanes and Parmenides has unlimited length in time and space, but this Being has not got any form. According to this point of view, Xenophanes and Parmenides don't give this Being with shape of the sphere, but they just compare it with the sphere to reveal the perfection of such Being. We proved that Being of Xenophanes and Parmenides has unlimited length in time and space, but it has the form of the sphere. This state of affairs indicates the presence of the limitation of this Being and, therefore, the presence of actual contradiction. Discussion and conclusions: we have proved that main contradictions concerning the temporal and spatial infinity are not ultimately resolved in doctrine of Xenophanes and Parmenides from Elea and still exist as a field for further discussion.